HISTORY OF BACKGROUND OF THE ADMINISTRATIVE SERVICES PROVISION OF THE FOREIGN COUNTRIES - Kokhan, Bohdan (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2017)
Purpose: the article is devoted to the consideration of the history of the formation of the system of providing administrative services in foreign countries, taking into account the transition to a model of "service state", useful innovations, problems that arise during the reform of the system of providing administrative services. Methods: it also considers a different from the Ukrainian basic approach to the development of the system itself of the state apparatus and of individual bodies that provide administrative services in foreign countries. But the service ideology is considered as the theoretical basis of administrative services both in foreign countries. Results: process of developing administrative services in the theory of administrative law of different countries and in practice is a complex and multilevel process. Discussion: there are many ways governments have chosen to implement state programs by adjusting the system for providing administrative services. Providing services serves not only as an explicit process of interaction between the state and citizens, but also as a lever of influence, which the state can regulate social processes.